2020
DOI: 10.1017/s0954579420000590
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of gene-by-intervention studies of alcohol and other substance use

Abstract: Alcohol and other substance use problems are common, and the efficacy of current prevention and intervention programs is limited. Genetics may contribute to differential effectiveness of psychosocial prevention and intervention programs. This paper reviews gene-by-intervention (G×I) studies of alcohol and other substance use, and implications for integrating genetics into prevention science. Systematic review yielded 17 studies for inclusion. Most studies focused on youth substance prevention, alcohol was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 147 publications
(361 reference statements)
0
6
2
Order By: Relevance
“…The analysis thus did not confirm the hypothesis of a 'diathesis-stress'-type interaction found in several previous studies [7][8][9][10][11],…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The analysis thus did not confirm the hypothesis of a 'diathesis-stress'-type interaction found in several previous studies [7][8][9][10][11],…”
Section: Discussioncontrasting
confidence: 84%
“…Previous twin and molecular genetic studies investigating alcohol‐related gene–environment interactions with other environmental exposures have found that environments with more social control, for example in the form of romantic partnerships [7], religious [8] or rural communities [9] and adolescent peer groups [10], attenuate the association between genetic susceptibility and alcohol use or the heritability of alcohol use. Furthermore, those with high genetic susceptibility may gain disproportionate benefits from targeted interventions such as health education or therapy [11]. These results give support to the ‘diathesis–stress’ model of gene–environment interactions, implying that when alcohol becomes less expensive and/or easier to acquire, genetic influences may become more pronounced [12–15].…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, many gene‐by‐environment interaction models are correlational and do not allow causative conclusions (and some are prone to problems, van der Sluis et al., 2012, and some are simply wrong and should not be used, e.g., Duncan & Keller, 2011), however they begin to give us evidence to allow us to characterize groups of individuals who may be vulnerable for school difficulties based on environmental factors. Newer approaches to gene‐by‐environment interaction models, which include using genomic data and randomized controlled trial methods, can help us understand for whom and when an environmental intervention works or what environments matter the most (e.g., Burgoyne et al., 2020; Harden & Koellinger, 2020; Neale et al., 2021). These newer variations of gene‐by‐environmental interactions are very powerful in understanding the causal role of the environment (e.g., Neale et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Newer approaches to gene‐by‐environment interaction models, which include using genomic data and randomized controlled trial methods, can help us understand for whom and when an environmental intervention works or what environments matter the most (e.g., Burgoyne et al., 2020; Harden & Koellinger, 2020; Neale et al., 2021). These newer variations of gene‐by‐environmental interactions are very powerful in understanding the causal role of the environment (e.g., Neale et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…van Ijzendoorn and Bakermans‐Kranenburg (2015) conducted a meta‐analysis to examine the magnitudes of GxI interaction effects from 22 psychosocial, behavioral, and cognitive intervention studies. The other review primarily focused on alcohol and substance use as the outcome of interest (Neale et al, 2020).…”
mentioning
confidence: 99%